Aspek Hukum Pengikatan Jual Beli Tanah Petok D Menurut Kuhperdata - Alur Anzarwati Sekoningtias; Nynda Fatmawati Octarina (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The sale and purchase of land rights has been regulated in Government Regulation Number 24 of 1997 concerning Land Registration. Fulfillment of all requirements related to the implementation of buying and selling before a notary, a legal breakthrough was found and until now it is still carried out in the practice of buying and selling land, namely by making a binding deed of sale and purchase agreement (PPJB). This research is a type of normative legal research, namely research in which researchers examine document studies using various secondary data such as legislation on court decisions and legal theory. Based on the results of the study that the characteristics of the land sale and purchase agreement with the status of petok D follow the general provisions of the agreement law as regulated in Article 1457 of the Civil Code. It's just that the object of sale and purchase of land has the status of Petok D, then the procedure for the agreement is applied using provisions that are more specific in nature, namely guided by Government Regulation Number 24 of 1997 concerning land registration.Keywords: Sale and Purchase of Land Petok D, Sale and Purchase Binding Agreement. Abstrak Jual beli hak atas tanah telah diatur dalam Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah. Pemenuhan terhadap semua persyaratan yang berkaitan dengan pelaksanaan jual beli dihadapan notaris, maka ditemukan suatu terobosan hukum dan hingga kini masih dilakukan dalam praktek jual beli tanah yaitu dengan dibuatnya akta pengikatan perjanjian jual beli (PPJB). Penelitian ini merupakan jenis penelitian hukum normatif yakni penelitian dimana didalamnya peneliti mengkaji studi dokumen yakni menggunakan berbagai data sekunder seperti perundang-undangan keputusan pengadilan dan teori hukum. Berdasarkan hasil penelitian bahwa Karakteristik perjanjian jual beli tanah yang berstatus petok D mengikuti ketentuan umum hukum perjanjian sebagaimana yang telah diatur didalam Pasal 1457 KUHPerdata. Hanya saja obyek jual beli tanah berstatus petok D maka diberlakukan tata cara perjanjian dengan menggunakan ketentuan yang sifatnya lebih khusus yaitu berpedoman pada Peraturan Pemerintah Nomor 24 tahun 1997 tentang pendaftaran tanah.Kata Kunci : Jual beli tanah petok D, Perjanjian Pengikatan jual beli